Annual Plan 1983-84 Government of the Union Territory of Goa, Daman, and Diu - Planning Commission (Planning Commission, 1983)
The Planning Commission approved a total outlay of Rs. 192.00 crore for the Sixth Five Year Plan of Goa, Daman and Diu beginning from the year 1980-81. The year 1983-84 is the fourth Year of the Sixth Five Year Plan. During the first 3 years investment has been stepped Up proportionately from Rs. 31.25 crore in 1980-81, Rs. 34.50 crore in 1981-82 to Rs. 44.12 crore in 1982-83. During the first three years i.e.. 1980-81, 1981-82 and 1982-83 the actual plan expenditure incurred was Rs. 31.70 crore, Rs. 37.67 crore and Rs. 48.95 crore. The expenditure figure during 1982-83 is yet to be reconciled and it includes the expenditure on works covered under CHOG-M (83) programme.
Directorate of Planning, Statistics and Evaluation